The Influence of Trust, Perceived Ease of Use, Perceived Usefulness, Perceived Enjoyment on Intention to Use TikTok Shop through Attitude Towards Using as Mediation - Dandi; Erlita Ridanasti (PT SOLUSI EDUKASI BERDIKARI, 2024)
TikTok is a globally popular social media from China, it also has a huge influence in Indonesia. TikTok has many interesting features, one of which is a shopping feature called TikTok Shop. The aim of this research is to examine the influence of trust, perceived ease of use, perceived usefulness, perceived enjoyment so that it can increase intention to use with an attitude towards using as mediation. The research method uses a quantitative approach by distributing questionnaires to 150 respondents who use the TikTok application in Indonesia. Data analysis was carried out using PLS-SEM with SmartPLS 4.1.0.6 software. The research results stated that the variables trust, perceived ease of use, and perceived enjoyment had a positive and significant effect on attitude towards using. On the other hand, perceived usefulness does not have a positive and significant effect on attitude towards using. The research results also state that attitude towards using has a positive and significant effect on intention to use.